Patient Involvement in Anesthesia Decision-making: A Qualitative Study of Knee Arthroplasty. (July 2021) - Graff, Veena; Clapp, Justin T.; Heins, Sarah J.; Chung, Jamison J.; Muralidharan, Madhavi; Fleisher, Lee A.; Elkassabany, Nabil M.
Abstract : Background: Calls to better involve patients in decisions about anesthesia— e.g., through shared decision-making—are intensifying. However, several features of anesthesia consultation make it unclear how patients should participate in decisions. Evaluating the feasibility and desirability of carrying out shared decision-making in anesthesia requires better understanding of preoperative conversations. The objective of this qualitative study was to characterize how preoperative consultations for primary knee arthroplasty arrived at decisions about primary anesthesia. Methods: This focused ethnography was performed at a U.S. academic medical center. The authors audio-recorded consultations of 36 primary knee arthroplasty patients with eight anesthesiologists. Patients and anesthesiologists also participated in semi-structured interviews. Consultation and interview transcripts were coded in an iterative process to develop an explanation of how anesthesiologists and patients made decisions about primary anesthesia. Results: The authors found variation across accounts of anesthesiologists and patients as to whether the consultation was a collaborative decision-making scenario or simply meant to inform patients. Consultations displayed a number of decision-making patterns, from the anesthesiologist not disclosing options to the anesthesiologist strictly adhering to a position of equipoise; however, most consultations fell between these poles, with the anesthesiologist presenting options, recommending one, and persuading hesitant patients to accept it. Anesthesiologists made patients feel more comfortable with their proposed approach through extensive comparisons to more familiar experiences. Conclusions: Anesthesia consultations are multifaceted encounters that serve several functions. In some cases, the involvement of patients in determining the anesthetic approach might not be the most important of these functions. Broad consideration should be given to both the applicability and feasibility of shared decision-making in anesthesia consultation. The potential benefits of interventions designed to enhance patient involvement in decision-making should be weighed against their potential to pull anesthesiologists' attention away from important humanistic aspects of communication such as decreasing patients' anxiety. Abstract : In a qualitative study of 36 anesthesia consultations before knee arthroplasty, it was found that the anesthesia consultation is complex with multiple functions and involvement in shared decision-making may not be the most important function of the visit. Shared decision-making may be limited by external factors and the risk of increasing preoperative anxiety.Supplemental Digital Content is available in the text.